Serviços de redes sociais para disseminação de informações de saúde em sistemas de monitoramento remoto de pacientes - Ribeiro, Hugo de Almeida (2018)
Healthcare demand is expected to surpass healthcare offer in the next years, encumbering the healthcare system. In one side we have an increase in life expectancy, and therefore the occurrence of chronic diseases, while on the other side we have a shortage of healthcare professionals. Remote patient monitoring systems can be used to continuously keep track of a person health status. When integrated to social networking services, we can build a carer network around the patient. This network is composed of formal (healthcare professionals) and informal carers (family and friends). Information regarding the patient health status can be disseminated within the carer network. Then the remote patient monitoring system may instruct informal carers to assist the patient before recommending formal care. Thus reducing the demands over the healthcare system. There are research initiatives on health information dissemination using social networking. But these initiatives are isolated. This dissertation aims to propose a domain model and an architectural model for remote patient monitoring systems that integrate social networking services unifying concepts found in state-of-the-art literature. The proposed solution is based on three sub-domains: remote patient monitoring systems, enable continuous health status monitoring; social networking services, allow actors to show interest in monitoring other actors health status; and event notification systems, distribute health information among actors. An skeletal system was built to validate the proposal. This skeletal systems consists on modifying an existing system to satisfy restrictions imposed by the proposed models and an usage scenario.